TI_GERICHTE 16.2015.38 vom 25. Oktober 2017 , Mutuo - diritto di essere sentito - diritto di ottenere una decisione motivata - TI Tribunale d'appello (2017)
Mutuo - diritto di essere sentito - diritto di ottenere una decisione motivata